Corruption In Morocco-A Sectorial Analysis - Igbida, Issam; Essaid, Tarbalouti (Institut Agama Islam Negeri Ponorogo, 2024)
Corruption, a pervasive socio-economic problem, has a significant impact on Morocco, reflecting a global challenge that undermines trust in public institutions and hinders development. This phenomenon, often defined as the abuse of public power for private gain, results in widespread citizen distrust of their government and public institutions. Recognizing the critical need to address this issue, Morocco has implemented various strategies and reforms at the institutional and civil society levels to combat corruption. Our study aims to provide a sectoral analysis of corruption in Morocco, assessing the prevalence of corrupt practices and the effectiveness of anti-corruption measures put in place. Using a descriptive methodology, our research relies on secondary data from various databases, including Transparency International's Corruption Perceptions Index (CPI) from 2004 to 2023. This index provides a longitudinal perspective on how perceptions of corruption have evolved in Morocco over the years and serves as a key indicator of the effectiveness of anti-corruption efforts. Our findings indicate that despite these efforts, corruption remains entrenched in several sectors, suggesting that the strategies adopted have not yet succeeded in significantly changing the corruption landscape. This analysis underscores the complexity of fighting corruption in Morocco and highlights the need for continued efforts and innovative strategies to effectively address this endemic problem.